Translating the Next Sentence: Language as Theme in Some Poetry of Manfred Jurgensen - Perkins, Elizabeth (LiNQ (Literature in North Queensland), 2016)
Manfred Jurgensen has been writing poetry in English since 1961 when, at the age of twenty-one he migrated as a student to Melbourne from his native Ftensburg in north-western Germany. In 1985, Waiting for Cancer, his sixth collection of poems in English, was published by the Queensland Community Press.